Development of interactive augmented reality mobile application for learning Jawi - Siti Hasnah Tanalol; Nur Hasyimah Abdul Halim; Asni Tahir; Aslina Baharum; Jetol Bolingkikit (Pusat e-pembelajaran, UMS, 2022)
The development in the technology of smart electronics devices is now undeniable as it has changed the lifestyle and at the same time, it has raised the usage of technology today. Advances in new technologies have changed many aspects of lifestyle and impacted various sectors including education as the world is growing. However, applications that can help children learn Jawi are extremely lacking. Therefore, the project proposes an AR Mobile Apps-based application to offer users an easy and effective way to learn Jawi. The main goals in the construction of this project include engaging children and regardless of community age in learning Jawi while at the same time removing the perceptions of some people who think that studying Jawi is for certain specific groups only. Other than that, the focus of this project is to examine the implementation of a multi-marker in AR for learning. In addition, the project is an upgrade from the previous application system where improvements lead to how multi-marker detection techniques can be applied in augmented reality technology for PintAR Jawi.